Descriptive Study of Gender Dysphoria and Sexual Behavior in a Disorder of Sex Development Group - Bridi Filho, Cesar Augusto; Cardoso, Saulo Batinga; Soll, Bianca Machado Borba; Noal, Marcelo Fröelich; Schwarz, Karine; Rosito, Tiago Elias; Rosito, Nicolino Cesar; Lobato, Maria Inês Rodrigues (Frontiers in Psychology, 2022)
Disorder of Sex Development (DSD) refers to a heterogeneous group of congenital conditions in which chromosomal, gonadal, and anatomical sex are atypical. Typically, the diagnosis is made at birth or infancy and interventional actions are necessary in many cases. The repercussions in adult life, more specifically in the field of sexuality, have not been not widely studied yet. This study shows research data that seek to identify in a group of individuals with DSD (XX DSD, XY DSD, Chromosomal DSD), who are being monitored in the departments of pediatric surgery and urology of a hospital in the period from 2000 to 2019, and to verify the consequences on sex life after puberty. The sample has 16 participants (7 XY DSD, 4 XX DSD and 5 Chromosomal DSD), aged between 16 and 50 years, single, with high school education, residents of the state capital and countryside of the state. The results depict the presence of a case of Gender Dysphoria; postponement of sexual debut for almost three years compared to the national average; a single sexual relationship for those who have already had a sexual experience with penetration; penis size below the general population average; presence of masturbatory activity in most participants. The presence of sexual attraction and masturbation indicate sexual desire. The group has a late onset of sexual life (almost three years after the national average). A recurrent feature in this group is that, even having already performed a penetrative sexual act, there is no continuation in their sexual life. The main noticeable aspect about Gender Dysphoria is the presence of only one case of incongruence in the Chromosomal DSD group. The limited sample prevents us from sufficient statements for generalization.